Listening to silence in Spanish and English-medium instruction online lectures - Querol-Julián, Mercedes; Amondarain-Garrido, Maite (Routledge, 2025)
This chapter presents a comparative study of the episodes of interaction that took place in two live online lessons given by the same lecturer. They belong to two parallel international master’s degree programmes, one given in Spanish (L1) and the other in English (L2). It explores the influence that teaching through English as a lingua franca has on the EMI live online lecture. We are particularly concerned about how lecturer’s and students’ silence is integrated and how students’ stillness is managed during the episodes of interaction. A multimodal discourse analysis perspective was adopted to study participants’ silence and the strategies the lecturer used to repair students’ stillness. The analysis showed some differences between the two lectures in the length and frequency of the periods of silence and how students’ participation was fostered. Results revealed major implications for EMI lecturer training regarding the importance of silence management in the virtual environment.
Keywords: EMI; live online lectures; interaction; silence; multimodal discourse analysis; Scopus